Рост молоди пиленгаса (Liza haematocheilus) в Азово-Черноморском бассейне - (:unkn) unknown (My University, 2009)
Прослежены внутригодовые и межгодовые изменения средних размеров сеголетков и двухлетков пиленгаса в северо-западной части Азовского моря и в Чёрном море у побережья Севастополя. Интенсивный рост рыб отмечен с мая по ноябрь. К началу зимы общая длина сеголетков из Азовского моря составила в среднем 8.9 см, масса – 9.15 г. Перезимовавшие годовики имели такую же длину, а их масса уменьшилась до 7.5 г. В Чёрном море поздней осенью сеголетки были длиной 7.7 см, массой – 6.9 г. Размеры двухгодовиков существенно варьировали в разные годы, составив в северо-западной части Азовского море в среднем 26.3 см и 197.4 г, в Чёрном море (возле Севастополя) – 22.9 см и 116.8 г.
Growth of young haarder (Liza haematocheilus) in the Azov-Black Sea region
Intra- and interannual changes in the mean size of one year and 2-years old haarders were studied in the northwestern part of the Azov Sea and the Black Sea off the coast of Sevastopol. Intensive growth of the fish occurred since May to November. The total length of fingerlings to beginning of the winter was on average 8.9 cm in the Sea of Azov, weight – 9.15 g. After winter yearlings had the same length but their weight decreased to 7.5 g. Fingerlings from the Black Sea were 7.7 cm and 6.9 g in late autumn. The sizes of 2-years old fish considerable varied in different years averaged 26.3 cm and 197.4 g in the northwestern part of the Sea of Azov and 22.9 cm and 116.8 g in the Black Sea (near Sevastopol).
Keywords: пиленгас; молодь; рост; Азовское море; Черное море